2021
DOI: 10.1021/acs.organomet.1c00330
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reactivity with tBuCN of a Thorium Phosphinidiide through a Combined Experimental and Computational Analysis

Abstract: An investigation of the formation of a thorium phosphinidiide reveals that changing from a 2,4,6-iPr3C6H2 (Tipp)-substituted phosphido ligand to a 2,4,6-Me3C6H2 (Mes) ligand forms a similar product, [(C5Me5)2Th]2(P-2,6-CH2C6H2-4-CH3), but via a different sequence of bond activations. The resulting phosphinidiide was reacted with 1 and 2 equiv of tBuCN, leading to mono­(ketimide), [(C5Me5)2Th]2[μ2-P-(2-CH2-6-(NC­(tBu)­(CH2))-4-Me-C6H2)], and bis­(ketimide), [(C5Me5)2Th]2[μ2-P-(2,6-(NC­(tBu)­(CH2))2-4-Me-C6H2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…We surveyed the literature and selected a range of representative compounds that were structurally characterized, have clear 31 P NMR data, and cover the range of dative single bond phosphines, covalent single bond phosphanides, covalent double bond phosphinidenes, and covalent triple bond phosphidos. In addition to 1 – 4 , this adds an additional 57 complexes to the analysis, spanning Th, Sc, Ti, Zr, Nb, Mo, W, Re, Ru, Os, Co, Rh, Ir, and Ni metals, all computed at the same B3LYP level as 1 – 4 , Table S6. ,,,,,,,,, We thus plotted δ iso values vs computed MBOs for a wide range of Th and groups 3–10 of the transition metals, Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We surveyed the literature and selected a range of representative compounds that were structurally characterized, have clear 31 P NMR data, and cover the range of dative single bond phosphines, covalent single bond phosphanides, covalent double bond phosphinidenes, and covalent triple bond phosphidos. In addition to 1 – 4 , this adds an additional 57 complexes to the analysis, spanning Th, Sc, Ti, Zr, Nb, Mo, W, Re, Ru, Os, Co, Rh, Ir, and Ni metals, all computed at the same B3LYP level as 1 – 4 , Table S6. ,,,,,,,,, We thus plotted δ iso values vs computed MBOs for a wide range of Th and groups 3–10 of the transition metals, Figure .…”
Section: Resultsmentioning
confidence: 99%
“…It is also the case that many An complexes are paramagnetic, so the range of diamagnetic An–P derivatives is relatively limited, and although Th­(IV) is diamagnetic, its bonding is usually more ionic than that of, for example, U, and hence synthesizing and isolating stable Th–ligand multiple bond linkages is often more challenging for the larger Th compared to U on HSAB and steric reasons. Furthermore, to realistically use 31 P NMR spectroscopy for covalency studies a family of related molecules with varied An–P bond types is required to rigorously construct the necessary framework approach where a single molecular example would not suffice, and there are relatively few complexes with direct An–P bonds that can be described as meeting that criterion. It is also the case that An–P bonds are generally prone to decomposition in the presence of air or moisture, making studies more experimentally challenging to undertake. Lastly, another challenge of incorporating 31 P NMR as a tool for studying An-covalency is that the 31 P nucleus is exceedingly sensitive to its environment (bond lengths, hybridization, molecular dynamics, formal molecule charge, phase, solvent), which can render rigorous and systematic understanding challenging to acquire, again highlighting the need for structurally related An–P molecules from which to validate the use of 31 P NMR spectroscopy in probing covalency.…”
Section: Introductionmentioning
confidence: 99%
“…Walensky and co-workers also derivatised 53 to synthesise the bridging phosphide/phosphinidiide thorium complex [{Th(Cp*) 2 (μ-PTripp)(μ-PHTripp)(K)} 2 ] ( 58 ), Scheme 17, 87 which paved the way to a number of derivatives. 88–92 The reaction of 53 with one equivalent of KN(SiMe 3 ) 2 gave 58 in a yield of 64% via the elimination of one equivalent of HN(SiMe 3 ) 3 . It was found that if the deprotonation reaction was conducted in the presence of 2.2.2-cryptand the monomeric phosphide/phosphinidene complex [K(2.2.2-cryptand)][Th(Cp*) 2 (PTripp)}(PHTripp)] ( 59 ) was obtained.…”
Section: Actinide Phosphorus Complexesmentioning
confidence: 99%
“…Complexes containing metal–ligand multiple bonding continue to enhance our understanding of the molecular and electronic structures of the actinides . This is especially true of the pnictogen group, for which actinide–imido complexes have been studied for 3 decades, while studies involving actinide–phosphinidene or phosphinidiide moieties are less studied but are becoming more common. In recent years, several examples of other actinide–main group bonds have been reported, with both thorium­(IV) and uranium­(VI) having diamagnetic ground states, affording bonding information by combining structural and spectroscopic techniques with density functional theory (DFT) calculations. However, no such study has been conducted with f element–phosphorus bonds.…”
Section: Introductionmentioning
confidence: 99%